Multi-omics reveals the phyllosphere microbial community and material transformations in cigars - Wang, Xiaoyu; Yang, Shuai; Gao, Qiang; Dai, Youqing; Tian, Lei; Wen, Liang; Yan, Honghao; Yang, Long; Hou, Xin; Liu, Peng; Zhang, Li (Frontiers in Microbiology, 2024)
The quality of fermented plant leaves is closely related to the interleaf microorganisms and their metabolic activities. In this experiment, a multi-omics analysis was applied to investigate the link between the structural composition of the phyllosphere microbial community and the main metabolites during the fermentation process. It was found that the whole fermentation process of cigar leaves could be divided into three stages, in which the Mid-Stage was the most active period of microbial metabolic activities and occupied an important position. Staphylococcus, Brevundimonas,